Resilience of Indonesia’s Trade Balance to Short-Term Exchange Rate and Inflation Dynamics - Andreas Panjaitan; Suny Sabila; Septri Anisa; Debora Silvia Hutagalung; Artha Putri Br Karo (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
Indonesia's trade balance is often considered vulnerable to exchange rate fluctuations and inflation, but in reality, the period from January 2023 to December 2024 showed a surprising pattern. This study uses a quantitative approach with multiple linear regression on monthly data from Bank Indonesia and Statistics Indonesia to examine the short-term effects of the exchange rate and inflation. The results show that neither is significantly affected. Despite a moderate depreciation of the rupiah and a decline in inflation to its lowest level in history, the trade balance remains in surplus. This finding challenges the common assumption that short-term macroeconomic fluctuations determine trade performance and reveals that structural external factors such as global commodity prices and trading partner demand play a more dominant role. This study emphasizes the need for innovative sector-based trade strategies beyond conventional monetary instruments to maintain external stability.